Service Orientation in Holonic and Multi-Agent Manufacturing - Borangiu, Theodor; Trentesaux, Damien; Thomas, André; McFarlane, Duncan (Studies in Computational Intelligence,, 2016)
This volume gathers the peer reviewed papers which were presented at the 5th edition of the International Workshop "Service Orientation in Holonic and Multi-agent Man-ufacturing - SOHOMA'15" organized in November 5-6, 2015 by the Institute for Manufacturing (IfM) of the University of Cambridge, UK in collaboration with the CIMR Research Centre in Computer Integrated Manufacturing and Robotics of the University Politehnica of Bucharest, Romania, the LAMIH Laboratory of Industrial and Human Automation Control, Mechanical Engineering and Computer Science of the University of Valenciennes and Hainaut-Cambrésis, France and the CRAN Re-search Centre for Automatic Control, Nancy of the University of Lorraine, France. The book is structured in seven parts, each one grouping a number of chapters de-scribing research in actual domains of the digital transformation in manufacturing and trends in future manufacturing control: (1) Applications of Intelligent Products; (2) Advances inControl of Physical Internet and Interconnected Logistics; (3) Sustaina-bility Issues in Intelligent Manufacturing Systems; (4) Holonic and Multi-agent Sys-tem Design for Industry and Services; (5) Service Oriented Enterprise Management and Control; (6) Cloud and Computing-oriented Manufacturing; (7) Smart Grids and Wireless Sensor Networks. These seven evolution lines have in common concepts, methodologies and imple-menting solutions for the Digital Transformation of Manufacturing. The book offers an integrated vision on complexity, big data and virtualization in service- and compu-ting-oriented manufacturing, combining emergent information and communication technologies, control with distributed intelligence and MAS implementation for total.